Consequences of allostatic load in chronic combat stress - M. B. Patsenko; E. G. Ichitovkina; A. G. Likholetov; M. I. Pugachev; O. Yu. Patsenko (Clinical Medicine (Russian Journal), 2026)
Relevance. Chronic combat stress (CCS) is a special form of long-term stress exposure associated with the formation of initially borderline functional states, subsequently remote mental and somatic disorders in war veterans. Current data indicate the systemic nature of these disorders in the form of the formation of pre-clinical manifestations and going beyond isolated mental pathology. Objective. Systematic analysis and meta-analytic evaluation of longitudinal studies devoted to the remote mental and somatic consequences of chronic combat stress from the standpoint of the allostatic load concept. Material and methods. A systematic review and meta-analysis of longitudinal cohort studies published in 2010–2025 were performed. The search was conducted in the PubMed/MEDLINE and Scopus databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The analysis included studies with a quantitative assessment of combat exposure and mental or somatic outcomes. The meta-analytic synthesis was performed using the random eff ects model; Heterogeneity was assessed using the I² and τ² statistics. Results . Forty-two studies were included in the fi nal analysis. CСS is associated with an increased risk of developing posttraumatic stress disorder (PTSD), depressive and anxiety disorders, as well as cardiovascular diseases, metabolic and endocrine disorders. Signs of persistent autonomic, neuroendocrine, and immune dysregulation were identifi ed. Genetically informed studies confi rm a partial commonality of the biological determinants of mental and cardiovascular disorders. Conclusions. CСS should be considered as a multilevel pathogenetic factor in the formation of remote mental and somatic consequences, which justifi es the need for an interdisciplinary approach to the management of this category of patients.